2016
DOI: 10.1097/qad.0000000000001252
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and HIV coinfection in Europe

Abstract: Objective:To better understand the epidemiology of tuberculosis (TB)/HIV coinfection in the European Union (EU) and European Economic Area (EEA) for planning of prevention and control measures.Design:Analysis of surveillance data.Methods:We performed an analysis of the 2014 TB and AIDS data to assess the burden of TB/HIV coinfection and we applied multivariable logistic regression to evaluate predictors for coinfection.Results:Twenty-one of 31 EU/EEA countries reported HIV testing results for 64.6% of the 32 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 28 publications
1
6
1
2
Order By: Relevance
“…A high rate of TB/HIV co-infection was also observed in patients <15 years of age. This is in contrast to several studies that have shown TB/HIV coinfection rates to be higher in persons aged 25–45 years [ 10 , 21 , 22 ] representing the sexually active age group. The high prevalence in persons <15 years could imply early indulgence in sexual activities by this age group in the study districts but this needs to be thoroughly investigated.…”
Section: Discussioncontrasting
confidence: 99%
“…A high rate of TB/HIV co-infection was also observed in patients <15 years of age. This is in contrast to several studies that have shown TB/HIV coinfection rates to be higher in persons aged 25–45 years [ 10 , 21 , 22 ] representing the sexually active age group. The high prevalence in persons <15 years could imply early indulgence in sexual activities by this age group in the study districts but this needs to be thoroughly investigated.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the sub-group analysis, the HIV infection rate among TB patients was highest among children under 15 years of age (30.1%) followed by people between 25 and 44 years. This finding is consistent with previous finding from the same study region [26] and that of other reports that have shown higher rate in persons aged 26-45 years who represent the sexually active age group [31,32]. Contrary to the previous report [26] however, males had the highest TB/HIV coinfection rate (30.6%) compared to 17.9% among females in this study.…”
Section: Hiv Test Among Tb Patients and Tb/hiv Co-infection Ratesupporting
confidence: 92%
“…Nas evidências alcançadas percebeu-se que, apesar de muitos casos com AIDS, há uma notificação substancial de casos de TB pulmonar. Resultados semelhantes foram encontrados em outros estudos [21][22][23][24][25] , porém a forma extrapulmonar é comumente em PVHA, tendo em vista, que em imunodeprimidos os bacilos adentram à corrente sanguínea e espalham-se por outros órgãos 26 . Desta forma, torna-se necessário o desempenho de medidas educativas que incentivem a adesão ao tratamento do HIV/Aids, a fim de manter adequada a contagem das células de defesa, Linfócitos CD4+.…”
Section: Resultsunclassified